Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1002/1097-0142(197303)31:3<502::aid-cncr2820310303>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Chlorambucil vs. combined chlorambucil-corticosteroid therapy in chronic lymphocytic leukemia

Abstract: Eleven patients with chronic lymphocytic leukemia were treated with chlorambucil alone and 15 patients received combined chlorambucil‐prednisone therapy in a double‐blind study. Mean age, duration of disease, physical findings, and hematologic data in the two groups were essentially comparable. Complete remission was observed in 3 and partial remission in 10 of the patients in the chlorambucil‐prednisone treated group; but only one of the patients obtained complete and four showed partial remission with chlora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(43 citation statements)
references
References 12 publications
1
38
0
2
Order By: Relevance
“…Typical dose-response curves are shown for Chl in from the dose-response curves which gave a scatter of results in accordance with clinical experience of response (Desai et al, 1970;Han et al, 1973;Liepman & Votaw, 1978;Oken & Kaplan, 1979;Sawitsky et al, 1977) success of the assay was 100%, and this included repeat assays of the previous 3 patients whose cells were non-viable after 4 days in culture. Assays were often performed on cells taken from the same patient on consecutive visits to the hospital.…”
Section: Drug Concentrationsfor Use In Vitrosupporting
confidence: 61%
“…Typical dose-response curves are shown for Chl in from the dose-response curves which gave a scatter of results in accordance with clinical experience of response (Desai et al, 1970;Han et al, 1973;Liepman & Votaw, 1978;Oken & Kaplan, 1979;Sawitsky et al, 1977) success of the assay was 100%, and this included repeat assays of the previous 3 patients whose cells were non-viable after 4 days in culture. Assays were often performed on cells taken from the same patient on consecutive visits to the hospital.…”
Section: Drug Concentrationsfor Use In Vitrosupporting
confidence: 61%
“…As early studies in patients with B-cell chronic lymphocytic leukemia (B-CLL) showed that addition of prednisone to chlorambucil augmented response rate but not median survival, glucocorticoids are not generally a standard component of initial therapy for patients with B-CLL (1,2). Nonetheless, two studies of high-dose glucocorticoid therapy have suggested that glucocorticoids can be of clinical benefit to a subset of patients with treatment-refractory B-CLL (3, 4).…”
mentioning
confidence: 99%
“…The waseiti e eWlecr greater stimulation of DNA cross-linking fThe sensidoled WaLkr and nuclear-protein phosphorylation than TI was doubled. CHL after treatment with the alkylating agent ximum tolerated dose of alone (Wilkinson et al, 1979 proved effective in combination with alkylating agents for the treatment of lymphomas (Jelliffe, 1975) and leukaemias (Han et al, 1973). In these cases the steroid alone is cytotoxic.…”
Section: Resultsmentioning
confidence: 99%